2021
DOI: 10.1111/jfb.14665
|View full text |Cite
|
Sign up to set email alerts
|

Coastal sharks and rays in a marine protected area in southernBrazil

Abstract: In southern Brazil, we investigated shark and ray capture records in an integral protection marine protection area (MPA) that allows fishing in that area. We found 10 shark and nine ray species, of which 88.5% and 66.2%, respectively, are endangered. Female adults and neonates of both sexes are abundant in the area, with records of stranding of large specimens, postcapture abortions and ovigerous capsules with fresh embryos on the beach. We suggest the application of continuous fisheries monitoring and an incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
1
3
0
2
Order By: Relevance
“…Our findings confirmed previous studies that reported capture of all three guitarfish species by recreational fishers in the same region, with low catches, particularly during warm months (Lewis et al., 1999; Motta et al., 2016; Peres & Klippel, 2005; Santos et al., 2021). However, scarce detailed catch information hinders assessment of the current status of recreational fishery harvest of guitarfishes.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings confirmed previous studies that reported capture of all three guitarfish species by recreational fishers in the same region, with low catches, particularly during warm months (Lewis et al., 1999; Motta et al., 2016; Peres & Klippel, 2005; Santos et al., 2021). However, scarce detailed catch information hinders assessment of the current status of recreational fishery harvest of guitarfishes.…”
Section: Discussionsupporting
confidence: 92%
“…Live M. thurstoni specimens were documented only in the SPSP and Fernando de Noronha archipelagos. The remaining 72 records were obtained from fisheries captures (Casas et al, 2006;Gadig et al, 2003;Jucá-Queiroz et al, 2008;Santos et al, 2021) Northeast Brazil (Jucá-Queiroz et al, 2008;Santander-Neto & Faria, 2020). This later record reinforces the possible connectivity between the oceanic islands in the Northeast and the continental shelf through the Fernando de Noronha Seamount Chain, as suggested for other elasmobranch species (Barcellos et al, 2022).…”
Section: Discussionmentioning
confidence: 69%
“…The sharks were concentrated mainly in insular areas within a mosaic of state (The São Paulo Marine Environmental Protection Area of the South Coast, APAMLS – Sustainable Use) and federal (The Tupiniquins Ecological Station, EETUPI – No Take/Integral Protection) protected marine areas (23 sharks – 76.67%), followed by captures of G. cirratum in nearby coastal regions, with gravel bottom (7 sharks – 23.33%). This result reinforces the benefits of MPAs for the conservation of species such as G. cirratum (and also of other elasmobranchs) (Bonnin et al ., 2021; Santos et al ., 2021; Motta et al ., 2022; Rolim et al ., 2022), as well as highlights the importance of the mosaics of protected areas to reduce conflicts between users, allowing certain activities such as fishing in some places and restricting its practice in others.…”
Section: Figurementioning
confidence: 99%